The Production of Insecurity by African Security Forces: Insights from Liberia and the Central African Republic - Andreas Mehler (German Institute of Global and Area Studies (GIGA), 2009)
Little attention has been paid to the factual effect of the state's security forces on the security of African citizens. Reports about security forces - contribution to widespread insecurity are frequent: the protectors become violators and their appearance causes fear, not security. In many African crisis countries the realization of better security forces appears to be an elusive goal, either because violent conflicts are not definitively settled and therefore do not allow for decent reform or because a lack of capacity as a result of material constraints is not easy to remedy. The self-help mechanisms used to compensate for the lack of state-sponsored security need more attention. However, it has to be acknowledged that the ideal of a neutral and effective force loyal to the state is shared by a great majority of the population. This contribution compares the experiences of Liberia and the Central African Republic, two extreme cases of strong and weak international involvement, respectively, in post-conflict security-sector reform. – – Die Produktion von Unsicherheit durch afrikanische Sicherheitskräfte: Einsichten aus Liberia und aus der Zentralafrikanischen Republik. Der tatsächliche Beitrag staatlicher Sicherheitskräfte zur Sicherheit afrikanischer Bürger wird selten erörtert. Es häufen sich die Berichte, wonach Sicherheitskräfte die schon existierende Unsicherheit erhöhen: die Beschützer werden zur Bedrohung und ihr Erscheinen erzeugt Angst, nicht Sicherheit. In vielen afrikanischen Krisenstaaten erscheint es als illusorisch, bessere Sicherheitskräfte zu bekommen, weil entweder die gewaltsamen Konflikte noch nicht endgültig beendet wurden und daher eine grundlegende Reform nicht möglich ist oder der Mangel an Kapazität lässt sich wegen materieller Engpässe nicht beheben. Selbsthilfemaßnahmen zur Kompensation der fehlenden staatlichen Sicherheitsgewährleistung verdienen größerer Aufmerksamkeit. Gleichzeitig muss anerkannt werden, dass eine große Mehrheit der Bevölkerung dem Ideal neutraler, effizienter und dem Staat gegenüber loyaler Sicherheitskräfte anhängt. Der vorliegende Beitrag vergleicht Erfahrungen in Liberia und in der Zentralafrikanischen Republik, zwei Extremfällen von massiver bzw. schwacher internationaler Einwirkung in die postkonfliktive Sicherheitssektorreform.
Keywords: 300; Liberia; Central African Republic; security; armed forces; security-sector reform